Age of the dacite of Sunset Amphitheater, a voluminous Pleistocene tephra from Mount Rainier (USA), and implications for Cascade glacial stratigraphy - Sisson, Thomas W.; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2019)
The dacite of Sunset Amphitheater, Mount Rainier (USA), illustrates the difficulties in establishing accurate ages of Pleistocene tephra eruptions. Nearly uniform whole-rock, glass, and mineral compositions, texture, and phenocryst assemblage establish that certain conspicuous dissected pumice exposures scattered from Mount Rainier to southern Puget Sound are products of the same Pleistocene Plinian eruption. Deposit thicknesses and pumice sizes support an eruption on the order of low Volcanic Explosivity Index (VEI) 5, atypically explosive for dominantly lava-producing Mount Rainier. Statistically permissible 40Ar/39Ar plateau ages of plagioclase phenocryst separates are 138±20ka and 101±11ka (2σ). A previously published result of 206±11ka is herein shown to result from a sample selection error. Zircon from the pumice yields a U-Th crystallization age of 147±8ka if the isochron is required to pass through the tephra U-Th isotopic composition. In contrast, pooled (U-Th)/He measurements on the zircon yield an age of 85±6ka (2σ), which accords with well-behaved 40Ar/39Ar ages of stratigraphically associated lavas high on Mount Rainier, and is the best estimate of the pumice's true eruption age. Inclusions of undegassed melt (glass) in the plagioclase separates are proposed as biasing apparent 40Ar/39Ar plateau ages to old values through coupling of undegassed magmatic excess Ar with radiogenic Ar that accumulated post-eruptively from relatively K-rich glass. U-Th ages record zircon growth prior to eruption, consistent with a possible complex history of advanced solidification followed by remobilization. The ca. 85ka eruption age confirms that bracketing glacial tills on the flanks of Mount Rainier were products of the Penultimate Glaciation (MIS 6) and Last Glacial Maximum (MIS 2). This eruption age also provides an important time marker for glacial and other sedimentary deposits in southern Puget Sound lowland that, excepting the Vashon Drift (MIS 2), generally lack reliable age determinations.
Gesehen am 03.07.2019